Assessment of potential for viral contamination of user and environment via aerosols generated during hand drying: A pilot study - Moura, Ines B.; Bentley, Karen; Wilcox, Mark H. (Frontiers in Public Health, 2022)
Background Hand drying is an essential step of hand hygiene, helping remove microbes remaining on hands following handwashing. However, it is unclear whether particles dispersed or aerosolized during hand drying can also have an impact on microbe dissemination and so pose an infection risk. Methods We used a PR772 bacteriophage to investigate whether microorganisms remaining on hands can disperse in the washroom environment and contaminate facemasks of others sharing the same space, as a surrogate for virus inhalation risk. Hand drying using either a jet air dryer or paper towels were performed, and mask contamination by splattering and droplet deposition was investigated, up to 15 min following each procedure. Results Facemask contamination by splattering was 10-fold higher when a jet air dryer was used, compared with hand drying by paper towels, for both the person performing the hand drying and for standby users stationed at 1 and 2 m distance. Facemask contamination by droplet/aerosols deposition was higher in the first 5 min following hand drying, for both methods; however, virus load was significantly higher when a jet air dryer was used. In the jet air dryer assays, facemask contamination increased at 15 min post-hand drying, suggesting aerosolization of small particles that remain airborne for longer. Conclusion When using a jet air dryer, virus contamination dispersed further and for a longer period of time (up to 15 min post hand-drying). The method chosen for hand drying can potentially impact the airborne dissemination of microbial pathogens, including respiratory virus, and so potentially increase the risk of exposure and infection for other washroom users.